The impact of the wine routes in the international promotion and exports of the Portuguese wine : the case of Península de Setúbal wine route - Costa, Manuel Maria Beirão de Oliveira Andrade da (2016)
The aim of this study is to examine the role of the wine routes as an international promoter and an export developer of wines. The focus will be in the Portuguese case, more specifically on Península de Setúbal Wine Route, also named Blue Coast Wine Route. Examining the wineries that are part of this route, the goal is to assess the impact of the route on the international image of the wines and exports and evaluate its importance and limitations.